A Quantitative Assessment of the Impact of Automated Incident Response on Cloud Services Availability (International Journal of Scientific Research and Management (IJSRM), 2023)
Abstract In the rapidly evolving landscape of cloud computing, ensuring high service availability is paramount for organizations reliant on digital infrastructure. This study conducts a quantitative assessment of the impact of Automated Incident Response Systems (AIRS) on the availability of cloud services. Utilizing a dataset derived from multiple cloud service providers over a twelve-month period, we analyze key performance metrics, including incident response times, resolution rates, and service uptime statistics, both pre- and post-AIRS implementation. The results indicate a statistically significant improvement in service availability following the deployment of AIRS, characterized by reduced incident resolution times and enhanced operational uptime. Furthermore, we present a comparative analysis of traditional incident response methodologies versus automated systems, demonstrating the superior efficiency and reliability of AIRS. The findings underscore the necessity for organizations to embrace automation in incident management to bolster service resilience and optimize customer satisfaction. This study concludes with practical recommendations for organizations considering the integration of AIRS into their operational frameworks. In the rapidly evolving landscape of cloud computing, ensuring high service availability has become a critical concern for organizations that depend heavily on digital infrastructures. This study conducts a comprehensive quantitative assessment of the impact of Automated Incident Response Systems (AIRS) on the availability of cloud services. As cloud environments become increasingly complex, the potential for service disruptions due to incidents—such as hardware failures, security breaches, or configuration errors—poses significant risks to businesses. Through a detailed analysis of incident response metrics obtained from a diverse dataset comprising five leading cloud service providers, this research evaluates key performance indicators including incident response times, resolution rates, and service uptime statistics over a twelve-month period. Employing rigorous statistical methods, the study investigates the relationship between the implementation of AIRS and enhancements in service availability, offering insights into the effectiveness of automation in incident management. The results reveal a statistically significant improvement in service availability post-AIRS deployment, characterized by a dramatic reduction in average incident response times—from 30 minutes to just 10 minutes—and an increase in resolution rates from 75% to 95%. Furthermore, the average service uptime improved from 90% to an impressive 99.5%, demonstrating the potential for organizations to achieve greater operational resilience through the integration of automated systems. The findings also include a comparative analysis of traditional versus automated incident response methodologies, highlighting the superior efficiency and reliability of AIRS. This study emphasizes the necessity for organizations to adopt automated solutions in their incident management frameworks to mitigate the risks associated with downtime and enhance customer satisfaction. The conclusions drawn from this research provide practical recommendations for businesses considering AIRS integration, making a compelling case for the strategic implementation of automated incident response mechanisms in the pursuit of optimal service availability.